The relationship between thyroid disorders and vitamin A.: A narrative minireview - Capriello, S.; Stramazzo, I.; Bagaglini, M. F.; Brusca, N.; Virili, C.; Centanni, M. (Frontiers in Endocrinology, 2022)
The terms “vitamin A” and “retinoids” encompass a group of fat-soluble compounds essential for human nutrition. Some of them (retinol, retinal, 9-cis-retinoic acid, tretinoin, and 13-cis-retinoic acid) are fully natural, while others are synthetic compounds used mostly for therapeutic purposes. Some evidence indicates that the nutritional status of these retinoids (i.e., the presence or absence of deficiency) is able to modulate thyroid gland metabolism. Vitamin A deficiency is tightly correlated with structural and functional impairment of the thyroid gland and is often associated with iodine deficiency. Furthermore, retinoids are involved in different immune functions, as well as in the process of activation, proliferation, and differentiation of regulatory T cells (Treg). This is particularly significant given the high prevalence of thyroid autoimmune disorders, whose pathogenesis seems to be related to the altered homeostasis of regulatory T cells. Retinoids are also involved in the modulation of gene expression via their interaction with nuclear receptors, and they also act as cofactors in cell growth and differentiation. The ability of retinoic acid to increase iodine uptake and sodium-iodine symporter activity in human thyroid cancer cell lines suggests that some retinoids and their derivatives may be of use in the treatment of different thyroid tumors. This minireview summarizes the current knowledge on the link between nutritional intake of vitamin A and various thyroid disorders.